Perancangan Media Pembelajaran Iqra Bagi Anak Usia Dini Berbasis Android - Ansori, Muhammad Fathul Huda; , Prof. Dr. Budi Murtiyasa M.Kom (2016)
Iqra is the simple alloy that consisting of 1 to 6 volumes to facilitate the learning to read Al Qur'an with practical and quickly. Iqro is step by step guide to recognizing the latters of Al Qur'an from the simple latters to the complex latters. The technological developments especially in the smartphone is very rapid, more over with the emergency of smartphone based on android which resultedin a decrease the interest in School Children to iqro as medium of learning. Android became a technology that used as an effective media learning iqro and raise that motivation to study for School Children, which contains letters and sound hijaiyah. This application using SDLC (System Development Life Cycle) methods which includes several stages, the several stages are needs analysis, design, testing and implementation. The making of this application is using android software studio as an application on android smartphone and construct 2 for the manufacture and processing data. In this apllication is included exercis to increase the understanding of the user to comprehendig the latter hijaiyah and the reading material of volmes 1,2,3,4,5 and 6. The retsults application of this study can be run android operating system 4.0 .3 (Ice Cream Sandwich) upwards.